Novel prototype tower structure for the dual-readout fiber calorimeter. (1st September 2022) - Karadzhinova-Ferrer, A.; Agarwala, J.; Ampilogov, N.; Chmill, V.; Ferrari, R.; Freddi, A.; Gaudio, G.; Gigli, S.G.; Samec, Ž.; Santoro, R.; Scagliotti, C.; Vercellati, F.
Abstract: In this paper, we report on a novel cost-effective module structure for future Dual-Readout fiber Calorimetry. We have designed and constructed the system required for the fabrication of the first proof-of-concept prototype module. The instruments, the procedures and the quality control tools used in the assembly of the prototype, and its equipment, are described exhaustively. A mechanical precision of 50 μm required for the interlocking of the tower structures into a compact module has been achieved. A similar system will be used for the assembly of a full-scale prototype based on the Dual-Readout technique.